VBBinaryLensing: a public package for microlensing light-curve computation - Bozza, Valerio; Hundertmark, Markus (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The computation of microlensing light curves represents a bottleneck for the modelling of planetary events, making broad searches in the vast paramet
Gesehen am 15.02.2019